Assessing the Implementation of the Audit Management Information System (SIMAUDI) in the Directorate General of Customs and Excise Using the DeLone and McLean Model - Pradana, Ardi Galung; Prasetya, Machmudin Eka (E-Jurnal Akuntansi, 2024)
A  Management  Information  System  (MIS)  provides  managers  with  essential  tools  and information to facilitate informed decision-making. This study evaluates the implementation of the Audit Management Information System (SIMAUDI) at the Directorate General of Customs and Excise (DGCE) using the DeLone and McLean Information System Success Model (ISSM). The research focuses on SIMAUDI users at the DGCE, including auditors, structural officials, and  staff,  with  respondents  selected  through  purposive  sampling  fromboth  the  DGCE Headquarters  and  Regional  Offices.  A  mixed-methods  approach  was  employed,  combining quantitative and qualitative methodologies. Data collection involved surveys, interviews, and document analysis to capture a comprehensive understanding of the system's effectiveness. The findings reveal that system quality enhances accessibility and reliability, though challenges with outdated data persist. Information quality supports audit monitoring but requires improvement to   ensure   timeliness.   Service   quality   expedites   technical   responses,   although   training opportunities remain limited. While system usage facilitates administrative tasks, its adoption is  still  constrained.  User  satisfaction  is  influenced  by  perceived  efficiency,  and  the  system's overall  impact  contributes  to  productivity  but  has  yet  to  significantly  reduce  the  manual workload.   In   conclusion,   SIMAUDI   demonstrates   considerable   potential   to   improve accountability  and  transparency  in  the  audit  process.  However,  regular  evaluation  and continuous improvements are essential to optimize its performance and fully realize its benefits.